2003
DOI: 10.1046/j.1460-9592.2003.t01-1-00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of QT Dispersion in Patients with Hypertrophic Cardiomyopathy

Abstract: QT dispersion is thought to reflect a regional difference in repolarization process although QT interval is composed of depolarization and repolarization. This study was designed to investigate the effect of depolarization and repolarization on QT dispersion in hypertrophic cardiomyopathy. Standard 12-lead ECG was recorded in 70 hypertrophic cardiomyopathy patients with anteroseptal wall hypertrophy (HC-As), 8 patients with lateral wall hypertrophy (HC-L), 8 patients with diffuse hypertrophy (HC-D), and 46 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…β-blockers, amiodarone, calcium channel blockers, etc. ), as well as with a similar morphological pattern of LV wall hypertrophy [39,40,41]. In such a homogenous study sample, our data suggest the whole QT e dispersion as the best 12-lead surface ECG marker of NSVT risk compared with all the other QT subsegment dispersion values (QRS, QT p , T p T e , JT p , and JT e ).…”
Section: Discussionsupporting
confidence: 62%
“…β-blockers, amiodarone, calcium channel blockers, etc. ), as well as with a similar morphological pattern of LV wall hypertrophy [39,40,41]. In such a homogenous study sample, our data suggest the whole QT e dispersion as the best 12-lead surface ECG marker of NSVT risk compared with all the other QT subsegment dispersion values (QRS, QT p , T p T e , JT p , and JT e ).…”
Section: Discussionsupporting
confidence: 62%
“…The mechanism underlying the above-mentioned pathophysiological link might be only hypothesized. It is reasonable that, besides the hypertrophy magnitude per se, specific gene mutation, myocardial disarray, fibrosis, and mechanical dyssynchrony might impact on the myocardial repolarization lability and, hence, the whole QT spatial dispersion [22][23][24][25][26]. Supporting this hypothesis, we previously described a poor association between the MWT and QTcd, the latter strongly associated with an echocardiographic index of global systodiastolic ventricular performance, the myocardial performance index [13].…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, one study that enrolled people with HCM found an increased QRSv in the affected group only when 12-lead recordings were made. 26 In our study, we assessed only the limb leads, which may have compromised the results since the QRS interval duration is subject to alteration, being longer in the precordial leads. 27,28 The values for QTa and QTac were higher in cats with HCM, which has been previously reported in cats with left ventricular hypertrophy, 7 and also in humans with HCM, 29 who share relevant similarities in the manifestations of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study that enrolled people with HCM found an increased QRSv in the affected group only when 12-lead recordings were made. 26 In our study, we assessed only the limb leads, which may have compromised the results since the QRS interval duration is subject to alteration, being longer in the precordial leads. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%